2014
DOI: 10.5194/acp-14-4383-2014
|View full text |Cite
|
Sign up to set email alerts
|

Trends in new particle formation in eastern Lapland, Finland: effect of decreasing sulfur emissions from Kola Peninsula

Abstract: Abstract. The smelter industry in Kola Peninsula is the largest source of anthropogenic SO 2 in the Arctic part of Europe and one of the largest within the Arctic domain. Due to socio-economic changes in Russia, the emissions have been decreasing especially since the late 1990s resulting in decreased SO 2 concentrations close to Kola in eastern Lapland, Finland. At the same time, the frequency of new particle formation days has been decreasing distinctively at SMEAR I station in eastern Lapland, especially dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 42 publications
5
47
0
Order By: Relevance
“…It should also be noted that Asmi et al (2016) reported measuring particle diameters of 7 nm at Tiksi, whereas only those above 10 nm were reported in this study. NPF events were still observed at the subarctic stations Värriö, Pallas and Abisko during the darker months (November-February), though the fraction of event occurrence was typically much lower compared to other seasons (Kyrö et al, 2014;Asmi et al, 2011;Väänäinen et al, 2013). Notably, not a single event was observed at VRS, Station Nord, during the Arctic night in the absence of sunlight.…”
Section: Event Statisticsmentioning
confidence: 97%
“…It should also be noted that Asmi et al (2016) reported measuring particle diameters of 7 nm at Tiksi, whereas only those above 10 nm were reported in this study. NPF events were still observed at the subarctic stations Värriö, Pallas and Abisko during the darker months (November-February), though the fraction of event occurrence was typically much lower compared to other seasons (Kyrö et al, 2014;Asmi et al, 2011;Väänäinen et al, 2013). Notably, not a single event was observed at VRS, Station Nord, during the Arctic night in the absence of sunlight.…”
Section: Event Statisticsmentioning
confidence: 97%
“…A negative trend in N 100 was also reported for Europe over the same period, although observations were limited to five locations . Declining SO 2 emissions have also been linked to observed negative trends in sulfur dioxide concentrations, new particle formation, total PN, N 50 , N 80 , N 100 and N 150 at a site in northern Finland (Kyrö et al, 2014). Collaud found negative trends for scattering and absorption coefficients (mean −2 % yr −1 ) for locations in North America but no trend over Europe during the period 1996-2010.…”
Section: Effect Of Control Measuresmentioning
confidence: 99%
“…Saha et al (2018) reported that the regional NPF event frequency decreased from about 30% during 2001−2002 to about 10% during 2016 −2017 In Pittsburg, Pensylvania, in United States, accompanied by a strong decline in the SO 2 concentration of about 90% between these two time periods. Kyrö et al (2014) observed a strong decline (−3.7% yr −1 ) in the NPF event frequency at Värriö in Northern Finland over the time period of 1998−2011, and attributed this decline to decreasing sulfur emissions from the nearby industrial sources in the Kola Peninsula. Pallas, a site about 300 km west from Värriö, however, displayed no trend in the NPF event frequency during 2000−2010 .…”
Section: Temporal Characteristicsmentioning
confidence: 99%